2017
DOI: 10.3390/molecules22081331
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Anxiety Effect of (−)-Syringaresnol-4-O-β-d-apiofuranosyl-(1→2)-β-d-glucopyranoside from Albizzia julibrissin Durazz (Leguminosae)

Abstract: Albizzia julibrissin Durazz, a Chinese Medicine, is commonly used for its anti-anxiety effects. (−)-syringaresnol-4-O-β-d-apiofuranosyl-(1→2)-β-d-glucopyranoside (SAG) is the main ingredient of Albizzia julibrissin Durazz. The present study investigated the anxiolytic effect and potential mechanisms on the HPA axis and monoaminergic systems of SAG on acute restraint-stressed rats. The anxiolytic effect of SAG was examined through an open field test and an elevated plus maze test. The concentration of CRF, ACTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The OFT apparatus was a 180 cm diameter cylinder with 60 cm high walls. The center of the bottom of the apparatus had a 52 cm diameter section, as previously described [ 57 ]. The rats were placed into the same point of the field and were allowed to freely explore for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OFT apparatus was a 180 cm diameter cylinder with 60 cm high walls. The center of the bottom of the apparatus had a 52 cm diameter section, as previously described [ 57 ]. The rats were placed into the same point of the field and were allowed to freely explore for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The elevated plus maze was made of black plexiglas and consisted of two open arms (50.8 cm × 10.2 cm × 1.3 cm) and two closed arms (50.8 cm × 10.2 cm × 40.6 cm) that extended from a central platform (10.2 cm × 10.2 cm). The maze was elevated to a height of 72.4 cm above the floor [ 57 ]. After the OFT, rats were gently transported to the EPM room.…”
Section: Methodsmentioning
confidence: 99%
“…The major constituents of Bai-He and He-Huan-Pi have been reported to have antidepressant effects. 61 , 62 Two recent in vivo studies have revealed that He-Huan-Pi had an anti-anxiety effect via the regulation of neurotransmitters 63 and the serotonergic nervous system. 64 Additionally, a study used a Chinese formula that consisted of He-Huan-Pi, Suan-Zao-Ren, Bai-Shao and Bai-Zi-Ren using a depressed mice model indicated that this formula was able to reduce the immobility time of depressed mice by inhibiting the monoamine oxidase enzyme system, as well as by increasing serotonin and noradrenaline levels.…”
Section: Discussionmentioning
confidence: 99%
“…This antidepressant-like effect was reversed by treatment with a 5-HT 1A receptor antagonist but was not affected by treatment with 5-HT 1B or 5-HT 2A receptor antagonists; therefore, the plant extract seems to exert its antidepressant effects through 5-HT 1A receptors [48]. Several years later, Liu et al [49] determined that one of the active principles of this plant extract was the compound (−)-syringaresinol-4-O-β-D-apiofuranosyl-(1 → 2)-β-D-glucopyranoside (52, Fig. 6S, Supplementary Information), which increased the percentage of entries into and time spent on the open arms of the EPM while lowering the concentration of ACTH and corticosterone in plasma and decreasing the amount of neurotransmitters (DA, NA, 5-HT) and their metabolites in the cerebral cortex and hippocampus of treated rat brains.…”
Section: Experimental Studies In Animals or Cellsmentioning
confidence: 99%